Eksperimentasi Model PBL dan Model GDL Terhadap Kemampuan Pemecahan Masalah Matematis Ditinjau dari Kemandirian Belajar - Evi Yuliasari (Universitas PGRI Madiun, 2017)
This Research aims to determine the effect of problem-based learning model and guided discovery learning model of learning ability of students' mathematical problem-solving in terms of self-regulated learning. This was a quasi-experiment research. The sampling technique is multistage random sampling. The data collection technique is mathematical problem-solving ability test on essay form and questionnaire self-regulated learning of the student. Hypothesis testing using two-way ANOVA technique with 5% significance level. The conclusion of this research shows that (1) the mathematical problem-solving ability of students who are treated with PBL model is higher than the mathematical problem-solving ability of students who are treated with GDL model, (2) there is interaction effect between learning model and self regulated learning to mathematical problem solving abilities of student , (3) mathematical problem solving abilities treated by PBL model is higher than mathematical problem solving ability given GDL model in groups of students who have high self regulated learning, (4) there is no difference in mathematical problem-solving ability among students who are given Treatment of PBL models and treated with GDL models in groups of students who have low self-regulated learning.